Analysis of corrosion damage in a boiler made of AISI 304L stainless steel - Biljana Bobić; Bore Jegdić; Bojan Gligorijević (Zaštita Materijala)
The corrosion damage near the welded joint in the boiler of AISI 304L stainless steel was analysed. During welding, heat tint was formed near the weld on the inner surface of the boiler, because shielded gas was not applied. Due to the presence of heat tint and crevice in the welded joint, pitting corrosion occurred which caused the perforation and leakage of the boiler. Several procedures are proposed to prevent localised forms of corrosion (pitting and crevice corrosion) near the welded joint of the boiler.